RETRACTED: Exploration of Multiple Signaling Pathways Through Which Sodium Tanshinone IIA Sulfonate Attenuates Pathologic Remodeling Experimental Infarction - Mao, Shuai; Vincent, Matthew; Chen, Maosheng; Zhang, Minzhou; Hinek, Aleksander (Frontiers in Pharmacology, 2019)
The level of maladaptive myocardial remodeling consistently contributes to the poor prognosis of patients following a myocardial infarction (MI). In this study, we investigated whether and how sodium tanshinone IIA sulfonate (STS) would attenuate the post-infarct cardiac remodeling in mice model of MI developing after surgical ligation of the left coronary artery. All mice subjected to experimental MI or to the sham procedure were then treated for the following four weeks, either with STS or with a vehicle alone. Results of our studies indicated that STS treatment of MI mice prevented the left ventricular dilatation and improved their cardiac function. Results of further tests, aimed at mechanistic explanation of the beneficial effects of STS indicated that treatment with this compound enhanced the autophagy and at the same time inhibited apoptosis of the cardiomyocytes. Meaningfully, we have also established that myocardium of STS-treated mice displayed significantly higher levels of AMP kinase than their untreated counterparts and that this effect additionally associated with the significantly diminished activities of apoptotic promoters; mammalian target of rapamycin and P70S6 kinase. Moreover, we also found that additional administration of the AMP kinase inhibitor (compound C) or autophagy inhibitor (chloroquine) practically eliminated the observed the beneficial effects of STS. In conclusion, we suggest that the described multistage mechanism triggered by STS treatment enhanced autophagy thereby attenuating pathologic remodeling of the post-infarct hearts.